Fake news, phishing, and fraud: a call for research on digital media literacy education beyond the classroom. Issue 4 (2nd October 2018) - Lee, Nicole M.
ABSTRACT: The Internet poses a variety of risks at both the individual and societal levels including scams and the spread of misinformation. Older adults are especially vulnerable to many of these risks. This paper argues that one important strategy for combating such threats is through digital media literacy education. Although a good deal of research on digital media literacy for children exists, very little research exists on effective digital media literacy instructional interventions for adult populations. Specific directions for future research are offered.